If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + 33 = 7 + 5(4m + -2) Reorder the terms: 33 + 8m = 7 + 5(4m + -2) Reorder the terms: 33 + 8m = 7 + 5(-2 + 4m) 33 + 8m = 7 + (-2 * 5 + 4m * 5) 33 + 8m = 7 + (-10 + 20m) Combine like terms: 7 + -10 = -3 33 + 8m = -3 + 20m Solving 33 + 8m = -3 + 20m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-20m' to each side of the equation. 33 + 8m + -20m = -3 + 20m + -20m Combine like terms: 8m + -20m = -12m 33 + -12m = -3 + 20m + -20m Combine like terms: 20m + -20m = 0 33 + -12m = -3 + 0 33 + -12m = -3 Add '-33' to each side of the equation. 33 + -33 + -12m = -3 + -33 Combine like terms: 33 + -33 = 0 0 + -12m = -3 + -33 -12m = -3 + -33 Combine like terms: -3 + -33 = -36 -12m = -36 Divide each side by '-12'. m = 3 Simplifying m = 3
| -2v-8=-3v | | 18x=84-(7x+9) | | cot=-0.085 | | -19q+8(-4-7q)= | | x^2+kx+x+2k=0 | | x^3-9x=-6 | | 7-9j=4j-6 | | 7x=21-(49x-63) | | x^2-4x+y^2+z^2-6z-3=0 | | T^2+16t-36=0 | | 5-8u=-7u | | 8t-9=10t+9 | | 5x=31+2x+11 | | 6x+10-3x=8+2x-5 | | -r^2+8r=0 | | 2cosx-5=0 | | 3y+9=2y-4 | | 6+10-3x=8+2x-5 | | Y=5z-8 | | 15x+3(4x-6)=3x+9-9x | | (2x-4)+X=28 | | 7x=5+3x+19 | | 8h=10h+6 | | x^2-2x=19 | | 20+7n-6=7(2n+4) | | (x+14)(2x-7)=0 | | -5g=-10-3g | | x^2-2x=16 | | 5x+9=2x+48 | | 12=3(y-6)+3y | | -5q=-3q+10 | | 52x^2+13=0 |